2013
DOI: 10.1155/2013/258758
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Sterilization of Anthracycline Antibiotics in Solid State

Abstract: The impact of ionizing radiation generated by a beam of electrons of 25–400 kGy on the stability of such analogs of anthracycline antibiotics as daunorubicin (DAU), doxorubicin (DOX), and epidoxorubicin (EPI) was studied. Based on EPR results, it was established that unstable free radicals decay exponentially with the half-time of 4 days in DAU and DOX and 7 days in EPI after irradiation. Radiation-induced structural changes were analyzed with the use of spectrophotometric methods (UV-Vis and IR) and electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…The findings of the present study are in accordance with the published report which illustrated no change in the pH of irradiated sulphonamide [20]. However, the earlier study demonstrated the formation of free radicals by analogs of anthracycline followed by e-beam irradiation at 25 kGy [21]. Further, the complex-free radicals formed following the gamma irradiation of penicillin derived antibiotics at 25 kGy were decreased with storage time of 80 d [22].…”
Section: Discussionsupporting
confidence: 92%
“…The findings of the present study are in accordance with the published report which illustrated no change in the pH of irradiated sulphonamide [20]. However, the earlier study demonstrated the formation of free radicals by analogs of anthracycline followed by e-beam irradiation at 25 kGy [21]. Further, the complex-free radicals formed following the gamma irradiation of penicillin derived antibiotics at 25 kGy were decreased with storage time of 80 d [22].…”
Section: Discussionsupporting
confidence: 92%
“…Electron paramagnetic resonance (EPR) spectroscopy is a known electromagnetic technique used for recording paramagnetic centers, such as free radicals [1][2][3][4][5]. Thus, it has application in different research fields like medicine and pharmacy, for example, to characterize the mechanism of pharmacological action of drugs or to estimate the effect of radiation on drug delivery system and also on its stability in solid state and in aqueous solutions, respectively [1,[6][7][8][9][10][11][12][13]. Recently, the current literature review proves various applications of EPR spectroscopy in pharmacy, for example, to examine the stability of UV irradiated and thermally sterilized drugs, especially antibiotics [6,13] and glucocorticosteroids [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has application in different research fields like medicine and pharmacy, for example, to characterize the mechanism of pharmacological action of drugs or to estimate the effect of radiation on drug delivery system and also on its stability in solid state and in aqueous solutions, respectively [1,[6][7][8][9][10][11][12][13]. Recently, the current literature review proves various applications of EPR spectroscopy in pharmacy, for example, to examine the stability of UV irradiated and thermally sterilized drugs, especially antibiotics [6,13] and glucocorticosteroids [7]. Because the sterilized antibiotics, especially coming from anthracycline family, such as doxorubicin, daunorubicin, epidoxorubicin, are widely applied in anticancer therapy (e.g., in leukemia and breast cancer) [13], there is a need to examine their vulnerability to thermal and UV irradiation prior use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The We used FTIR to study the structural characteristics of the DOX/DAU:POSS complexes in PBS (pH 7.4) after 24 h at 310 K ( Figure 3). The FTIR spectrum of DOX indicated the characteristic peaks at 3523 cm −1 (ν O-H ); 3321 cm −1 (ν O-H , ν N-H ); 2974, 2954, 2932 and 2896 cm −1 (ν O-H , aromatic ring), 1724 cm −1 (ν C=O , ketone); 1616 (sc, NH 2 ), 1580 cm −1 (ν C=C , aromatic ring); 1525 cm −1 (δ C-O-H , aromatic ring); 1413 cm −1 (δ O-C-H ; δ N-C-H ); 1283 cm −1 (ν C-O-H , aromatic ring); 1201 cm −1 (ν C-O , glycosidic bond); 1234 cm −1 (δ C-O-H , COCH 2 OH group) and 1205 cm −1 (δ CO-H , aromatic ring in DAU); and 1191 cm −1 (ν C-O , glycosidic bond in DAU) [20]. In contrast, the DOX:POSS spectrum indicated that peak intensities at 1525 cm −1 (δ C-O-H , aromatic ring), 1723 cm −1 (ν C=O , ketone), 1234 cm −1 (δ C-O-H , COCH 2 OH group), 1283 cm −1 (ν C-O-H , aromatic ring) and 1201 cm −1 (ν C-O , glycosidic bond) decreased.…”
Section: Resultsmentioning
confidence: 99%